2019
DOI: 10.1002/jsfa.9877
|View full text |Cite
|
Sign up to set email alerts
|

Residue behaviours, dissipation kinetics and dietary risk assessment of pyaclostrobin, cyazofamid and its metabolite in grape

Abstract: BACKGROUND Grape is an important fruit consumed either fresh or processed, therefore, fungicide misuse of grape has become an issue of global food safety and human health. Pyraclostrobin, and cyazofamid have been applied to grape frequently. RESULTS Here a simple QuEChERS (quick, easy, cheap, effective, rugged, and safe) liquid chromatography mass spectrometry technique has been developed and validated for the determination of pyraclostrobin, cyazofamid and its metabolite CCIM in open field grape samples. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 27 publications
(56 reference statements)
1
17
0
Order By: Relevance
“…The dissipation behavior and residue of methoxyfenozide have been further revealed through open field trials. Furthermore, a risk assessment was carried out based on the risk quotient (RQ) method, also known as the hazard quotient (HR) method . This study not only contributes to establishing a reasonable Chinese MRL for methoxyfenozide but also provides practical data on its safe use.…”
Section: Introductionmentioning
confidence: 99%
“…The dissipation behavior and residue of methoxyfenozide have been further revealed through open field trials. Furthermore, a risk assessment was carried out based on the risk quotient (RQ) method, also known as the hazard quotient (HR) method . This study not only contributes to establishing a reasonable Chinese MRL for methoxyfenozide but also provides practical data on its safe use.…”
Section: Introductionmentioning
confidence: 99%
“…Pang et al . reported the dietary risk assessment of pyaclostrobin in grape based on the results of field trials in Shandong 16 . In 2017, Kabir et al .…”
Section: Introductionmentioning
confidence: 99%
“…Pang et al reported the dietary risk assessment of pyaclostrobin in grape based on the results of field trials in Shandong. 16 In 2017, Kabir et al determined the residual amounts of picoxystrobin in oriental melon in two different sites and assessed the long-term risks. 15 These articles focused more on fruits, and the risk assessments for pyraclostrobin and picoxystrobin on cucumber were not researched.…”
Section: Introductionmentioning
confidence: 99%
“…However, the occurrence of disease in vineyards, especially fungal diseases, is one of the most significant economic losses [10]. Common fungal diseases of cultivated and wild grapes in world are grey mold (Botrytis cinerea), powdery mildew (Uncicula necator), and downy mildew (Plasmopara viti-cola) [11]. Cyazofamid, as showed in Figure 1A, presents strong activity against Plasmodium and Oomycetes and has been widely used to control a variety of fruit and vegetable diseases such as grape downy mildew (Plasmopara viti-cola) [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…So far, numerous researchers have studied the changes of pesticide residues in wine processing [31][32][33]. To our knowledge, many studies have reported on the residues of cyazofamid and its metabolite, CCIM, in the field [10,11,34], but little attention has been paid to the change in their residue levels caused by the process of wine-making. In order to guarantee food safety for consumers, we utilized grapes harvested in the field to carry out wine-making processing experiments.…”
Section: Introductionmentioning
confidence: 99%